Automated quantification system predicts survival in rheumatoid arthritis-associated interstitial lung disease. (18th March 2022) - Oh, Ju Hyun; Kim, Grace Hyun J; Cross, Gary; Barnett, Joseph; Jacob, Joseph; Hong, Seokchan; Song, Jin Woo
Abstract: Objective: The prognosis of RA-associated interstitial lung disease (RA-ILD) is difficult to predict because of the variable clinical course. This study aimed to determine the prognostic value of an automated quantification system (AQS) in RA-ILD. Methods: We retrospectively analysed the clinical data and high-resolution CT (HRCT) images of 144 patients with RA-ILD. Quantitative lung fibrosis (QLF, sum of reticulation and traction bronchiectasis) and ILD [QILD; sum of QLF, honeycombing (QHC), and ground-glass opacity (QGG)] scores were measured using the AQS. Results: The mean age was 61.2 years, 43.8% of the patients were male, and the 5-year mortality rate was 30.5% (median follow-up, 52.2 months). Non-survivors showed older age, higher ESR and greater AQS scores than survivors. In multivariable Cox analysis, higher QLF, QHC and QILD scores were independent prognostic factors along with older age and higher ESR. In receiver-operating characteristic curve analysis, the QLF score showed better performance in predicting 5-year mortality than the QHC and QGG scores but was similar to the QILD score. Patients with high QLF scores (≥12% of total lung volume) showed higher 5-year mortality (50% vs 17.4%, P  < 0.001) than those with low QLF scores and similar survival outcome to patients with idiopathic pulmonary fibrosis (IPF). Combining with clinical variables (age, ESR) further improved the performance of QLF score in predicting 5-year mortality. Conclusion: QLF scores might be useful for predicting prognosis in patients with RA-ILD. High QLF scores differentiate a poor prognostic phenotype similar to IPF.